Laser direct patterning of AgNW/CNT hybrid thin films. (October 2015) - Yoon, Ji-Wook; Chang, Won Seok; Cho, Sung Hak
Abstract: A hybrid material composed of silver nanowires (AgNWs) and carbon nanotubes (CNTs) is investigated by a laser direct patterning method. A femtosecond laser system with a wavelength of 1027 nm and a pulse width of 380 fs is applied for the patterning of AgNW/CNT hybrid film. The Gaussian and square quasi-flat-top beam profiles are used for the patterning lines. The laser fluence and overlapping rate were optimized for patterning at 67.9 mJ/cm 2 and 70%, respectively. The patterned AgNW/CNT film is evaluated using an optical microscope and scanning electron microscope. The partially ablated area of AgNW/CNT films around the patterned line is observed and discussed. The measurement results explain that the uniformity of the laser beam profile and the beam shape are key factors for development of AgNW/CNT films with fine edges. Highlights: The AgNW/CNT hybrid film was patterned using a femtosecond laser direct patterning technique. The Gaussian and square quasi-flat-top beam profile was applied for patterning line. The AgNW/CNT film patterning using the square quasi-flat-top beam profile had finer edge shape and less partially ablated area near the patterned. The uniformity of the beam energy distribution and the shape of the focused beam were key factors for patterning of the AgNW/CNT with fine edge qualities.